2021
DOI: 10.1093/ije/dyab168.052
|View full text |Cite
|
Sign up to set email alerts
|

85An Outbreak Of Foodborne Illness, Boamang-Kyerekrom D/A Primary School, Afigya Kwabre North District, Ghana

Abstract: Background On 6th June 2019, Afigya Kwabre North District Health Administration reported suspected foodborne illness involving primary school pupils at Boamang Kyerekrom D/A Primary School. Investigation was done to identify risk factors and implement control and preventive measures. Methods We conducted active case search and a retrospective cohort study. A case was a person from Boamang presenting with fever, diarrhea, or/a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…The attack rate of 12.1% in this outbreak was lower than what was reported in Boamang Kyerekrom D/A primary School in the Afigya Kwabre North District of Ghana where an attack rate of 30.8 was reported (Laryea & Gyimah, 2021). Like that study, there were no mortalities reported.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…The attack rate of 12.1% in this outbreak was lower than what was reported in Boamang Kyerekrom D/A primary School in the Afigya Kwabre North District of Ghana where an attack rate of 30.8 was reported (Laryea & Gyimah, 2021). Like that study, there were no mortalities reported.…”
Section: Discussioncontrasting
confidence: 59%
“…In this study, cases showed multiple symptoms. In the study at Afigya Kwabre North District in Ghana, the commonest symptoms were abdominal pain, fever, nausea and bloody diarrhoea (Laryea & Gyimah, 2021). In this outbreak however, no bloody diarrhoea nor fever was reported.…”
Section: Discussionmentioning
confidence: 73%